2021
DOI: 10.5194/esurf-9-1073-2021
|View full text |Cite
|
Sign up to set email alerts
|

Sediment size on talus slopes correlates with fracture spacing on bedrock cliffs: implications for predicting initial sediment size distributions on hillslopes

Abstract: Abstract. The detachment of rock fragments from fractured bedrock on hillslopes creates sediment with an initial size distribution that sets the upper limits on particle size for all subsequent stages in the evolution of sediment in landscapes. We hypothesize that the initial size distribution should depend on the size distribution of latent sediment (i.e., fracture-bound blocks in unweathered bedrock) and weathering of blocks both before and during detachment (e.g., disintegration along crystal grain boundari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Bimodality in granitic sediment has commonly been attributed to granular disintegration caused by biotite weathering (Buss et al., 2008; Shen et al., 2019; Wahrhaftig, 1965), which would tend to be enhanced at lower elevations in the catchment, where temperatures are warmer and vegetation is denser. Conversely, at higher elevations, where slopes are steeper and frost cracking is more common (Riebe et al., 2015), a diversity of processes produce a range of sizes, including abundant gravel and cobbles (Sklar et al., 2020), from a latent size distribution that is set by the fracture spacing of the underlying bedrock (Verdian et al., 2021). This sediment is then abraded and fractured as it travels downstream to the outlet, and thus the source elevations inferred from ages in stream sediment fail to match the observations of sediment size from hillslopes at higher elevations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bimodality in granitic sediment has commonly been attributed to granular disintegration caused by biotite weathering (Buss et al., 2008; Shen et al., 2019; Wahrhaftig, 1965), which would tend to be enhanced at lower elevations in the catchment, where temperatures are warmer and vegetation is denser. Conversely, at higher elevations, where slopes are steeper and frost cracking is more common (Riebe et al., 2015), a diversity of processes produce a range of sizes, including abundant gravel and cobbles (Sklar et al., 2020), from a latent size distribution that is set by the fracture spacing of the underlying bedrock (Verdian et al., 2021). This sediment is then abraded and fractured as it travels downstream to the outlet, and thus the source elevations inferred from ages in stream sediment fail to match the observations of sediment size from hillslopes at higher elevations.…”
Section: Discussionmentioning
confidence: 99%
“…Direct measurements of sediment size distributions from other mountain landscapes confirm that such spatial variations in sediment production may be common (Sklar et al., 2017) and thus should be expected in applications of detrital thermochronology. For example, size distributions of sediment produced on hillslopes have been shown to correlate with variability in lithology (Lai et al., 2021; Roda‐Boluda et al., 2018), erosion rate (Riebe et al., 2015; Whittaker et al., 2010), topography (Attal et al., 2015), fracture spacing (Neely & DiBiase, 2020; Verdian et al., 2021), climate (Marshall & Sklar, 2012; Terweh et al., 2021), and geomorphic processes (Roda‐Boluda et al., 2018; Sklar et al., 2017, 2020). In mountain landscapes, where many of these factors often vary across individual catchments, different sediment sizes at the outlet may reflect sediment production from different parts of the catchment, where lithologic, climatic, and topographic conditions favor different sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that the grain size distribution of coarse sediment delivered from steep hillslopes to channels can be dependent on bedrock fracture spacing ( 15 , 16 ), bedrock tensile strength ( 14 ), and grain size reduction during mass wasting ( 39 ). In the Taiwan Central Range, there is limited variation in bedrock compressive strength among major units ( 40 ), and we interpret the boulder size signal as corresponding to a decrease in the effective fracture density with increasing metamorphic grade.…”
Section: Discussionmentioning
confidence: 99%
“…River morphology can adjust through changes in both slope and width ( 10 ), and the partitioning between the two depends on sediment cover ( 11 ) and the erodibility of in-channel bedrock ( 12 ). Similarly, rock material strength sets the initial size distribution of sediment from hillslopes ( 13 ) through variations in lithology ( 14 ), fracture spacing ( 15 , 16 ), and the style of sediment delivery from hillslopes to channels ( 17 ). The role of boulders has been highlighted as a key linkage between bedrock fracture spacing, which sets boulder size ( 15 ), and channel width and slope, which are thought to be sensitive to boulder cover and size ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Grains form initially by fragmentation or chemical weathering, transforming a cohesive rock mass into a granular material. The initial size or shape distributions are controlled by fragmentation, weathering processes and structure of the rock mass (e.g., fracture density and orientation, mineral size) (e.g., Molnar et al, 2007;Garzanti et al, 2008;Sklar et al, 2017;DiBiase et al, 2018;Neely and DiBiase, 2020;Verdian et al, 2021). These initial distributions then evolve due to the action of geomorphological processes, including attrition, chipping, abrasion, fragmentation, chemical weathering and transport of grains by wind, river flow, avalanches along hillslopes, and sea waves and currents (e.g., Attal and Lavé, 2006;Domokos et al, 2014;Miller et al, 2014;Várkonyi et al, 2016;Novák-Szabó et al, 2018;Marc et al, 2021).…”
Section: Introductionmentioning
confidence: 99%